2014
DOI: 10.1038/ki.2013.394
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, impact, and treatment options of restless legs syndrome in end-stage renal disease patients: an evidence-based review

Abstract: Restless legs syndrome (RLS) (or Willis-Ekbom disease) is a neurological disorder with high prevalence among the end-stage renal disease population. This is one of the most predominant types of secondary RLS, and it is called uremic RLS. Despite the fact that uremic RLS has been less studied compared to idiopathic RLS, recent studies now shed light in many aspects of the syndrome including clinical characteristics, impact, epidemiology, and treatment options. The current review discusses the above topics with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
57
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 55 publications
4
57
1
2
Order By: Relevance
“…Several factors influence the severity of RLS such as hypertension, female gender, weight, dialysis shift, age, and diabetes in patients undergoing hemodialysis (1). The effects of dialysis modality and adequacy on the severity of RLS are controversial.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several factors influence the severity of RLS such as hypertension, female gender, weight, dialysis shift, age, and diabetes in patients undergoing hemodialysis (1). The effects of dialysis modality and adequacy on the severity of RLS are controversial.…”
Section: Introductionmentioning
confidence: 99%
“…There is a strong relationship between insomnia and depression, as insomnia is a symptom of depression and also a risk factor to deteriorate depression (9). There are reports on the correlation between RLS and mental health, depression, decreased quality of life, and increased mortality among patient underwent transplantation or undergoing hemodialysis (1,(10)(11)(12)(13)(14). RLS is one of the most powerful causes of insomnia in chronic kidney diseases, however, sleep disorder cause depression (11,15,16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] In addition, a review article noted the prevalence of "uremic RLS" was approximately 30% in endstage renal disease (ESRD) patients. [2] However, its prevalence in this group ranged between 6.6% and 80% in various reports. [3][4][5] Based on the International RLS Study Group (IRLSSG) criteria, an RLS prevalence of 33% has been reported in ESRD patients, which is greater than the normal population (3%-15%); [6,7] however, a study in Singapore showed lower prevalence in normal Asian population (0.1%-0.6%).…”
mentioning
confidence: 99%
“…In addition, RLS may represent a novel risk factor contributing to renal and cardiovascular damage [6, 7]. The reported prevalence of RLS among ESRD is as high as 30–50%; however, most surveys are based on self-administered questionnaires, without objective measures like polysomnography or even expert examination [8-12]. While Merlino et al [13] reported a 10.9% prevalence of RLS in non-dialysis chronic kidney disease (CKD) after expert investigation, we documented a 4.5% prevalence of RLS in this group of patients, similar to the frequency reported for the general population [13, 14].…”
Section: Introductionmentioning
confidence: 99%